Nonredundant roles of keratinocyte‐derived IL‐34 and neutrophil‐derived CSF1 in Langerhans cell renewal in the steady state and during inflammation. Issue 3 (28th December 2015) - Wang, Yaming; Bugatti, Mattia; Ulland, Tyler K.; Vermi, William; Gilfillan, Susan; Colonna, Marco
Abstract : Nonredundant functions of IL‐34 and CSF1 in Langerhans cells (LCs) renewal. In a fully differentiated and anatomically intact skin epidermis, keratinocytes produce IL‐34 to sustain the steady‐state renewal of LCs residing in the skin. In UV‐irradiated and inflamed skin, LC regeneration depends on CSF1 produced by infiltrating neutrophils. Abstract : IL‐34 and colony‐stimulating factor 1 (CSF1) are two alternative ligands for the CSF1 receptor that play nonredundant roles in the development, survival, and function of tissue macrophages and Langerhans cells (LCs). In this study, we investigated the spatio‐temporal production of IL‐34 and its impact on skin LCs in the developing embryo and adult mice in the steady state and during inflammation using Il34 LacZ reporter mice and newly generated inducible Il34 ‐knockout mice. We found that IL‐34 is produced in the developing skin epidermis of the embryo, where it promotes the final differentiation of LC precursors. In adult life, LCs required IL‐34 to continually self‐renew in the steady state. However, during UV‐induced skin damage, LC regeneration depended on neutrophils infiltrating the skin, which produced large amounts of CSF1. We conclude that LCs require IL‐34 when residing in fully differentiated and anatomically intact skin epidermis, but rely on neutrophil‐derived CSF1 during inflammation. Our demonstration that neutrophils are an important source of CSF1 during skin inflammation may exemplify a mechanism through which neutrophils promote their subsequent replacement with mononuclear phagocytes.